Building a Resilient Computer Emergency Response Team (CERT): A Strategic Approach Using SWOT Analysis and the CERT Resilience Maturity Model for Cybersecurity Preparedness in the Bangsamoro Government, Philippines (American Journal of Innovation in Science and Engineering, 2025)
exposed clients to risks during online transactions and service access. These incidents underscore the urgent need to enhance the region’s cybersecurity preparedness and establish a resilient Computer Emergency Response Team (CERT). This study evaluates the current state of cybersecurity readiness across selected Bangsamoro Government ministries, offices, and agencies by integrating SWOT analysis with the CERT Resilience Management Model (CERT-RMM). Through this structured approach, the study identifies key strengths, weaknesses, opportunities, and threats while determining the current maturity level of the government’s operational resilience. Based on the findings, actionable recommendations are provided to advance maturity levels and build a robust cybersecurity framework. The results aim to support the Bangsamoro Government in strengthening its digital infrastructure, ensuring secure service delivery, and mitigating emerging cyber threats effectively.